THE REPTILES - Carr, Archie, June 16, 1909 – May 21, 1987, author 649446; Time-Life Books 11642 (Hong Kong : Time-Life Books Inc., 1980)
Traces the evolution of reptiles and discusses the physical characteristics and habits of the three main groups existing today--turtles, lizards and snakes, and the crocodilians.